ALMAWARDI DAN KONSEP KHILAFAH ISLAMIYYAH: RELEVANSI SISTEM POLITIK ISLAM KLASIK DAN POLITIK MODERN - Muzayyin Ahyar (UIN Raden Mas Said Surakarta, 2018)
The long debate on the relevance of the concept of Islamic caliphate government to the modern political concept has been occurring among scholars up to nowadays. This situation leads to an important question about, to what extent the relevance/irrelevance of an Islamic political concept, when it is contextualized to the modern political conditions? This article aims to explore the source of Islamic political thought from the Classical Muslim intellectual; Almawardi and its contextualization to the modern political concepts. Through an in-depth literature study by using the political institutionalism approach, found out that the spirit of the classical Islamic political concept lies on the distribution of power which is not relevant to the spirit of power separation in the modern political concepts. Hereby, it can be emphasized that even if the concept of Khilafah which is promoted by the Islamic political activists basically out of date, but there were basic values related to the government administration and institution basically still relevance to the modern political concepts. The principle of justice, problem management, and transparency were generally still agreed by government ruler in this modern era.Â Â